Universal Investments in Toddler Health. Learning from a Large Government Trial - Jennifer L. Baker; Lise G. Bjerregaard; Christian M. Dahl; Torben S. D. Johansen; Emil N. Sørensen; Miriam Wüst (Institute of Labor Economics (IZA), 2023)
Exploiting a 1960s government trial in Copenhagen, we study the long-run and inter-generational effects of preventive care for toddlers. We combine administrative data with handwritten nurse records to document universal treatment take-up and positive health effects for treated children over the life course. Beneficial health impacts are largest for disadvantaged children and may even extend to their offspring. While initial trial cohorts experienced positive health and socioeconomic impacts, those are absent for the final cohorts. This heterogeneity across individuals' background and cohorts documents that universal toddler care can alleviate inequalities at low costs, and that the counterfactual policy environment matters.
Keywords: I1; J1; 330; early-life investments; health; public policy; government trial; Denmark; digitization; automated transcription